Chronology of the western world, 1500-1900 A.D. - Erdoes, Richard; Society for Visual Education (Chicago, Ill. The Society [production company], 1988)
Examines the western world and the achievements of its artists, scientists, politicians and philosophers. Looks at the exploration of the new world.
The Age of exploration and reformation, 1500-1750 A.D. (16 min.) -- Enlightenment, revolution and technology, 1750-1900 A.D. (16 min.)
Keywords: History, Modern